Current Status of Flowering Medicinal Plants Diversity of Delft Island - Sathiyaseelan, V.; Sathiyaseelan, T. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2013)
Delft Island is situated in the Palk Strait in the northern region of Sri Lanka. The objective of the present study was to conduct investigation of flowering medicinal plants biodiversity of Delft Island, and to identify the threats to its biodiversity. The study was conducted in April and November, 2011 through a five day field visit every month, which involved a rapid baseline biodiversity survey carried out to document the medicinal plants habitats of Delft Island. A total of 203 species of flowering medicinal plants representing diverse life forms were observed in the inland areas of the island, including three endangered medicinal plant species, 12 near threatened species and one endemic species were recorded. And to group them based on different categorization. This comprises of waste land medicinal plants (65%) wet pasture land medicinal plants (10%) and Sea coast medicinal plants (25%). Out of 203 medicinal plants 10 were seasonal medicinal plants. Based on the economically viable medicinal plants namely, Cassia obovata, Indigofera tinctoria, Solanum xanthocarpum and Plumbago zeylanica were recorded. Based on self-span perennials (60%), annual (33%) and biennials (7%). Ten percent poisonous plants were also recorded. Out of 203 plants, 10 in vatha diseases, 18 used for diabetic mellitus and 15 in treating skin diseases, and 15 for respiratory disorders. Further, grouping based on morphology revealed herbs (38%), trees (20%), shrubs (16%), climbers (12%), lianas (3%), creepers (8%), cacti (2%) and holo parasites (1%). Based on the usage of plant parts the plant species were grouped as whole plant (25), leaves (30), stems (15), and barks (28), rhizomes (08), galls (2), roots (30), dry fruits (4), young pods (06), flowers (10), seeds (12) and root barks (16). The Primary threats to the island are its biodiversity and overgrazing by cattle, invasive species of plants and fetching of for firewood. The present paper ends with a discussion on the conservation status of medicinal plants in Delft Island along with suggestion on the future course of actions.
Keywords: Delft Island; Medicinal plants; Diversity